2022
DOI: 10.1177/01445987221090364
|View full text |Cite
|
Sign up to set email alerts
|

Simulation and optimization of mining-separating-backfilling integrated coal mine production logistics system

Abstract: As a new collaborative mining technology, the integration of mining-separating-backfilling (IMSB) enables the coal industry to realize safe, efficient, and green mining of coal resources at the expense of making the underground coal mine production more complex. In coal mining, the primary problem is to eliminate the production logistics system bottleneck to increase coal output. The key to synergetic mining is to realize that the mining capacity of the fully mechanized face should match the underground raw co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…PCFM is combined with the bulkiness of loose rock, and the composite filling body formed by paste filling body and caving roof is used to support the overlying stratum (Yu et al, 2016; Yin et al, 2016; Guo, 2020; Lv et al, 2022), as shown in Figure 1. Compared with other filling methods, this filling method can also effectively reduce the filling cost, simplify the filling process, reduce the amount of filling materials, improve the filling speed, and minimize the impact on production (Xu et al, 2015; Yang et al, 2017; He et al, 2021; Qiu et al, 2022; Wang et al, 2022).…”
Section: Mechanical Model Analysismentioning
confidence: 99%
“…PCFM is combined with the bulkiness of loose rock, and the composite filling body formed by paste filling body and caving roof is used to support the overlying stratum (Yu et al, 2016; Yin et al, 2016; Guo, 2020; Lv et al, 2022), as shown in Figure 1. Compared with other filling methods, this filling method can also effectively reduce the filling cost, simplify the filling process, reduce the amount of filling materials, improve the filling speed, and minimize the impact on production (Xu et al, 2015; Yang et al, 2017; He et al, 2021; Qiu et al, 2022; Wang et al, 2022).…”
Section: Mechanical Model Analysismentioning
confidence: 99%
“…Coal is an important energy support for industrial development, with the continuous exploitation of mineral resources, the depth of mine mining is increasing, which prompts the continuous development and progress of mine hoisting and transport technology [1][2][3]. The mine hoisting system serves as a crucial transportation link in the coal production process.…”
Section: Introductionmentioning
confidence: 99%